Human rights monitoring in Africa : the African Peer Review Mechanism and the African Commission on Human and Peoples' Rights - Heyns, C.H. (Christof H.) (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2003.